2018
DOI: 10.1002/cphc.201701364
|View full text |Cite
|
Sign up to set email alerts
|

Optically Guided Single Cell Mass Spectrometry of Rat Dorsal Root Ganglia to Profile Lipids, Peptides and Proteins

Abstract: The mammalian dorsal root ganglia (DRG) are located on the dorsal roots of the spinal nerves and contain cell bodies of primary sensory neurons. DRG cells have been classified into subpopulations based on their size, morphology, intracellular markers, response to stimuli, and neuropeptides. To understand the connections between DRG chemical heterogeneity and cellular function, we performed optically guided, high-throughput single cell profiling using sequential matrix-assisted laser desorption/ionization mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 65 publications
0
49
0
1
Order By: Relevance
“…[6] While matrix-assisted laser desorption/ionization (MALDI) MS produces rich spectral profiles for label-free classifications, [7] the results can be difficult to correlate to canonical cell types. [8] Immunocytochemistry (ICC) is effective for classifying cells as it can target ap lethora of different molecules that distinguish cell types. [9] ICC has been combined with tissue imaging and af ew examples have coupled the method to single-cell MS. [10] However,f luorescence overlap of labels typically limits plexity to fewer than ten compounds, [11] and most ICC protocols require sample fixation and lipid removal, crosslinking and/or removing many compounds that are easily ionized by MALDI-MS. [12] Direct hyphenation of ICC and MS to analyze the same cell was reported in 2012, [10b] but ICC was performed first, limiting the analysis to high-abundance peptides within as mall number of cells.H erein, we describe aworkflow enabling high-throughput MALDI-MS analysis of thousands of cells,followed by cell classification through ICC.…”
mentioning
confidence: 99%
“…[6] While matrix-assisted laser desorption/ionization (MALDI) MS produces rich spectral profiles for label-free classifications, [7] the results can be difficult to correlate to canonical cell types. [8] Immunocytochemistry (ICC) is effective for classifying cells as it can target ap lethora of different molecules that distinguish cell types. [9] ICC has been combined with tissue imaging and af ew examples have coupled the method to single-cell MS. [10] However,f luorescence overlap of labels typically limits plexity to fewer than ten compounds, [11] and most ICC protocols require sample fixation and lipid removal, crosslinking and/or removing many compounds that are easily ionized by MALDI-MS. [12] Direct hyphenation of ICC and MS to analyze the same cell was reported in 2012, [10b] but ICC was performed first, limiting the analysis to high-abundance peptides within as mall number of cells.H erein, we describe aworkflow enabling high-throughput MALDI-MS analysis of thousands of cells,followed by cell classification through ICC.…”
mentioning
confidence: 99%
“…127 Laser desorption ionization (LDI) 128 and MALDI have also been used for single cell analysis. 124,[129][130][131] Conductive slides coated with hydrophobic laser-drilled cavities were used to organize cell smears in arrays (called microarrays for MS or MAMS), which were subsequently analysed by MALDI profiling of single cells. 129 Combined with automated smearing methods to deposit drug solution on surfaces, it has been demonstrated that MAMS would hold good promise for drug quantification.…”
Section: Therapies Applied To Circulating Cells: Ideal Models For Pmentioning
confidence: 99%
“…To expand optically guided, single-cell profiling beyond MALDI-TOFi nstrumentation, Comi et al [115] further developed the open source software,m icroMS,f or analyzing microscopy images and correlating cell locations to instrument positions.T he software provides automatic cell finding and filtering by attributes such as size,fluorescence intensity, and distance between cells,and is simple to tailor to avariety of instruments,e xpanding the availability of single-cell profiling.T he ease of switching between output coordinate systems also facilitates analysis of the same cell on multiple instruments;a ne xample being MALDI-TOFM Sa nalysis with follow-up CE-MS analysis ( Figure 6D). [115] Do et al [116] recently used microMS to set up sequential MALDI-MS analyses of rat DRG cells.Lipids,peptides,and small proteins were detected in the same cells,m any of which were not previously detected in tissue homogenates or releasates.T he DRG populations were stratified with multivariate statistical analysis using peptides and proteins as potential markers.A similar method utilizing flexImaging software from Bruker Corp.w as recently published by the Caprioli lab [117] to determine heterogeneity within cultured macrophage cells using aB ruker solariX XR FT-ICR mass spectrometer.T he authors imaged single cells by rastering across the slide and comparing the ion images with optical images acquired beforehand. They observed changes in lipid expression of macrophages upon chemical stimulation.…”
Section: Optically Guided Profilingmentioning
confidence: 99%